Analisis Kebutuhan Paket Pembelajaran dalam Konteks Pembelajaran Berbasis Project dalam meningkatkan keterampilan Abad 21 - Aswan, Dedy (Peneliti.net, 2024)
This study aims to analyze the needs of learning packages in the context of Project-Based Learning (PBL) and the challenges faced by students and teachers. Involving 100 students and 20 teachers from several schools that have implemented PBL, this research employs a mixed-methods approach using surveys and semi-structured interviews. The findings indicate that 75% of students feel more engaged in project-based learning, while 60% of them experience difficulties in managing time and resources. On the teacher side, 80% acknowledge an increase in student motivation, but 65% feel unprepared to design effective learning packages. This study identifies the need for clear guidelines, adequate resources, teacher training, and flexible assessment systems. The research concludes that to optimize the effectiveness of PBL, it is essential for schools to provide appropriate support to both teachers and students. Thus, project-based learning can be effectively implemented, equipping students with the necessary skills to face future challenges.